Mummies : Dried, Tanned, Sealed, Drained, Frozen, Embalmed, Stuffed, Wrapped, and Smoked...and We're Dead Serious (National Geographic Kids) - Sloan, Christopher; Terry, Robin (Washington, DC : National Geographic, 2010)
Investigate mysteries from the grave in this creepy-fun compendium of the world's most fascinating mummies. Learn what the experts have discovered about each mummy's life and death.
Keywords: Russian History -- non-fiction